2023
DOI: 10.32479/ijeep.14042
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Investment, Economic Growth, Renewable Energy, Urbanisation, and Tourism on Carbon Emissions: Global Evidence

Abstract: Examining urbanisation and tourism from the perspective of global Sustainable Development Goals is essential for achievinga balance between environmental protection and economic growth in the world's most polluted nations. Moreover, most polluted countries pay more attention to the nature of foreign direct investment (FDI) inflows to achieve a sustainableenvironment. This study intends to explore the impacts of FDI, tourism, urbanization, and economic growth on carbon dioxide emissions using panel data for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…CE and FDI also move in opposite direction as per the results of the study. High rate of pollution leads to lower rate FDI(Kayani et al 2023) and investors are not willing to invest in polluted and degraded environment and that is also validated by our empirics. GLOB is a boosting factor…”
supporting
confidence: 76%
“…CE and FDI also move in opposite direction as per the results of the study. High rate of pollution leads to lower rate FDI(Kayani et al 2023) and investors are not willing to invest in polluted and degraded environment and that is also validated by our empirics. GLOB is a boosting factor…”
supporting
confidence: 76%
“…The studies of Apergis et al [11], Kayani et al [41], and Wencong et al [42] found a positive association between foreign direct investment and carbon dioxide emissions.…”
Section: Resultsmentioning
confidence: 96%
“…The empirical study of Kayani et al [41] used panel cointegration to test the effects of FDI, renewable energy, urbanization, tourism arrivals, and economic growth on carbon dioxide emissions. The econometric results demonstrated that FDI, urbanization, economic growth, and tourism stimulate environmental degradation.…”
Section: The Role Of Foreign Direct Investment On Pollution Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonrenewable energy sources provide 85% of global energy consumption-from nonrenewable energy resources such as oil, coal, and natural gas. Education is a precondition for fast global economic growth (Kayani et al, 2023). Education promotes economic development and via various channels improves people's lives.…”
Section: Introductionmentioning
confidence: 99%